Recovery Time From Severe Community Acquired Pneumonia and Risk Factors Among Pediatrics, Ethiopia: A Retrospective Follow-Up Study - Addisu Dabi Wake MSc (SAGE Publishing, 2024)
Introduction . Severe community acquired pneumonia (CAP) is a life-threatening condition, with high rates of morbidity and mortality. This study aimed to determine the recovery time from severe CAP and risk factors among pediatric patients. Methods . A retrospective follow-up study was conducted among 412 pediatric medical charts with severe CAP enrolled at Asella Referral and Teaching Hospital between January 01, 2021 and December 31, 2022. EpiData version 4.6.0.6 and STATA version 14.2 were used for data entry and statistical analysis, respectively. Bivariable and multivariable Cox proportional hazards regression analyzes were performed. Result . The median recovery time from severe CAP among pediatric patients was 5 days (IQR = 3-8 days). IDR of recovery from severe CAP was 13.089 per 100 [95%CI: 11.82, 14.49] pediatric days observations. The cumulative incidence of recovery from severe CAP was 89.56% [n = 369, 95%CI: 86.20, 92.18]. Age [AHR = 1.55, 95%CI: 1.12, 2.13, P  = .007], vaccination status [AHR = 1.29, 95%CI: 1.03, 1.63, P  = .027], presence of danger signs [AHR = 1.61, 95%CI: 1.26, 2.05, P  = .000], presence of comorbidity [AHR = 1.67, 95%CI: 1.33, 2.10, P  = .000], duration of seeking care [AHR = 1.71, 95%CI: 1.18, 2.47, P  = .004], and oxygen therapy [AHR = 1.45, 95%CI:1.12, 1.87, P  = .004] were statistically significant risk factors for recovery time from severe CAP. Conclusions . The median recovery time of patients with severe CAP is relatively high. Age, vaccination status, presence of danger signs, presence of comorbidities, duration of seeking care, and oxygen therapy were statistically significant risk factors of recovery time from severe CAP.